Traditional rural dietary pattern and all-cause mortality in a prospective cohort study of elderly Costa Ricans: the Costa Rican Longevity and Healthy Aging Study (CRELES) - Zhang, Yundan (2024)
Costa Rica, as many other Latin American countries, is experiencing a fast demographic aging. It is estimated that by 2030, 18.5% of the population, or almost 1 of every 5 Costa Ricans, will be 60 y or older, compared with 7.9% or 1 of every 13 Costa Ricans in 1999 [1]. As the population ages, chronic health conditions such as cardiovascular diseases (CVDs) and neurodegenerative disorders are expected to increase in prevalence posing growing challenges to the health of the Costa Rican population. With the demographic shift toward an aging population, there is an urgent need to study determinants of longevity and healthy aging. Diet—as part of a healthy lifestyle—is a key modifiable factor that may help to minimize the burden of age-related health conditions. Beans are a major source of protein and fiber in Costa Rican adults and part of traditional diets in most Latin American countries. High bean consumption has been found associated with a protective cardiometabolic prolife such as low total cholesterol and LDL cholesterol [2,3]. In the Costa Rican population specifically, intake of beans has been associated with lower risk of nonfatal myocardial infarction in middle-aged adults [4]. We recently reported that a traditional Costa Rican rural dietary pattern, rich in beans and rice, was associated with longer leukocyte telomeres—a marker of biologic aging—in Costa Rican adults 60 y and older [5]. However, no studies have examined whether adherence to a traditional diet in elderly Costa Ricans may also be associated with lower mortality. Because of the nutrition transition (i.e., a shift from traditional diets to an increased consumption of processed foods highs in sugars, fats, and salt) experienced by Costa Rica in the last decades [4,6,7], it is essential to evaluate the potential impact of traditional diets on promoting healthy aging and longevity within an aging population. In this study, we assessed the association between a traditional rural dietary pattern, as well as their major food components beans and rice, and all-cause mortality among elderly Costa Ricans aged 60 y and older at baseline. We hypothesized that higher scores on the traditional dietary pattern are associated with lower all-cause mortality in elderly Costa Ricans. We also assessed whether additional dietary patterns may be associated with all-cause mortality. We used longitudinal and nationally representative data from the Costa Rican Longevity and Healthy Aging Study (CRELES).